Skin as a marker of internal disease: A case of sarcoidosis - Manjyot Gautam; Sharmila Patil; Pritam Munde (Wolters Kluwer Medknow Publications, 2011)
A 52-year-old female presented to our out patient department with asymptomatic, hypopigmented lesions on the neck and back since 2 months. There was a history of taking antitubercular treatment for suspected pulmonary tuberculosis 2 years back. On blood investigations, the serum angiotensin converting enzyme levels were increased and the skin biopsy revealed a naked granuloma in the dermis. A diagnosis of systemic sarcoidosis was made and the patient was started on oral corticosteroids and Methotrexate, with clinical improvement.